Design of Plastic Component Using Reverse Engineering Approach - G.Sreeram Reddy, Dr.; L.Madan Ananda Kumar, Dr. (International Journal of Engineering and Technology, 2018)
The Reverse Engineering (RE) technique for the design of plastic components of money counting machine using articulated laser scanner and CatiaV5 is presented.Â  Initially it is physically digitized to generate point cloud data with the help of a scanner through scanning and is exported to CAD software CatiaV5. Thus, this paper describes the processes of RE of plastic component from object digitization and analyze the error to reconstruct the CAD model. To study the behaviour of the component, the analysis has been performed with stress distribution, factor of safety and displacement of modified plastic component with existing one at minimum to maximum loads.Â